Primary Pelvic Involvement of Hydatid Disease - Migraci Tosun; Yıldırım Durak; Handan Çelik; Devran Bıldırcın; Mehmet Bilge Çetinkaya; Ali Faik Yılmaz (Medical Network, 2011)
Hydatid disease is caused by larval stage of a parasite named as Echinococcus. To diagnose this condition may be challenging without surgery and postoperative pathological examination due to limited value of serological studies but imaging techniques may give a clue when hydatid disease is suspected and hydatid disease shall be considered for differential diagnosis in pelvic mass. In the present case, we present a 75-year-old postmenopausal woman with pelvic hydatosis.